2023
DOI: 10.3389/fped.2023.1168173
|View full text |Cite
|
Sign up to set email alerts
|

Altered offspring neurodevelopment in an L-NAME-induced preeclampsia rat model

Abstract: IntroductionTo investigate the mechanism underlying the increased risk of subsequent neurodevelopmental disorders in children born to mothers with preeclampsia, we evaluated the neurodevelopment of offspring of a preeclampsia rat model induced by the administration of N-nitro-L-arginine methyl ester (L-NAME) and identified unique protein signatures in the offspring cerebrospinal fluid.MethodsPregnant rats received an intraperitoneal injection of L-NAME (250 mg/kg/day) during gestational days 15–20 to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…To verify our hypothesis, an oxidative stress model was established in HTR8/SVneo cell line by H 2 O 2 treatment to simulate the cellular microenvironment associated with PE, and we injected pregnant rats with L-NAME [21] , an endothelial nitric oxide synthase inhibitor, to establish a PE-like rat model. As expected, our study found elevated MDA levels and decreased SOD levels in the serum of PE rats, which is consistent with the pathophysiology of PE.…”
Section: Discussionmentioning
confidence: 99%
“…To verify our hypothesis, an oxidative stress model was established in HTR8/SVneo cell line by H 2 O 2 treatment to simulate the cellular microenvironment associated with PE, and we injected pregnant rats with L-NAME [21] , an endothelial nitric oxide synthase inhibitor, to establish a PE-like rat model. As expected, our study found elevated MDA levels and decreased SOD levels in the serum of PE rats, which is consistent with the pathophysiology of PE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the peak time for MBP expression in rodents is PND 20, after which expression stabilizes [ 50 ], if this is the case it might explain the lack of differences among our groups. Interestingly, PreE offspring (from the L-NAME model) that expressed impairments in spatial learning and memory, also had changes in cortical, hippocampal and striatal NeuN expression when assessed via immunohistochemistry [ 42 , 51 ]. The findings of no change in blood pressure among offspring from HDP dams in the current study is similar to another study with similar findings when offspring from PreE dams were examined [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, an increase in VEGF has been observed in PE-F1 mice, which could occur to compensate for the reduced levels of PGF [37]. A well-established and commonly employed method for inducing PE in mothers is through the administration of NG-nitro-L-arginine methyl ester (L-NAME) [90][91][92]. Research from our laboratory evaluated the effect of L-NAME-induced PE on offspring at an ontogenetic stage equivalent to childhood through the cerebellar expression of VEGF and two of its receptors, pY951 VEGF R2 and pY1172 VEGF R2.…”
Section: Vascular and Angiogenic Dysregulationmentioning
confidence: 99%